The Red Pony Movie Still - Chas. K. Feldman Group Productions, Incorporated; Republic Pictures; Viacom/Paramount Pictures:::Creator::::::::::::
Tom, aka Jody Tiflin (Peter Miles) stands at the gate with his fellow students, basking in the glory of prestige for owning the red pony. RESTRICTED USE